Operational auditing within Australian internal audit departments: Developing a framework - Vafaei, Elnaz (Curtin University, 2016)
This thesis identifies factors impacting the effective practice of Operational Audit (OA) in Australia within a holistic framework. Initially, a theoretical framework is developed by reviewing the literature and these framework factors are consequently confirmed or modified based on the results of 28 semi-structured interviews. The result from this thesis therefore is a multi-dimensional framework consisting of three constructs that assist organisations, practitioners and regulators in facilitating/improving their effective practice of OA.